An Analysis of Teacher’s Assessment Task in Teaching Writing at MAS TI Paninggahan - Ramadani, Nesi; Melani, Melyann; Eliza, Eliza; Irwandi , Irwandi (Journal of Educational Management and Strategy, 2023)
This research was conducted because of several problems found in class XI Mas.TI Paninggahan. Teachers tend to use monotonous assessment tasks, teachers do not assess assessment tasks well, students' motivation in learning to write English is low, teachers do not have enough time to see how students write. Students have problems in grammar and vocabulary. The purpose of this research is to find out what assessment tasks teachers give in teaching writing, to find out how teachers assess students' writing assessment tasks and then to find out what problems teachers have in assessing writing assessment tasks in class 11 MAS. IT Paninggahan. This research uses a qualitative descriptive method. Data obtained from interviews and document analysis were analyzed qualitatively. Researchers analyzed students' writing assessment assignments that had been given scores and interviews were conducted directly with the teacher. The findings from this research are several aspects of writing assessment tasks given by teachers in class activities during the second semester. There are several types of assessment tasks given by teachers in teaching writing. These are the cloze selection task, paragraph construction task, and guided question and answer. Furthermore, the researchers also found out about how teachers assessed the writing assessment tasks given. The assessment is carried out holistically by paying attention to the authenticity of the text, suitability of the text with the title, text order, choice of vocabulary, choice of grammar, vocabulary letters and neatness of the text. Each point was ranked by the researcher from five points to one point based on aspects of very suitable or not suitable.. Abstrak Penelitian ini dilakukan karena beberapa permasalahan yang ditemukan di kelas XI Mas.TI Paninggahan. Guru cenderung menggunakan tugas penilaian yang monoton, guru tidak melakukan penilaian tugas penilaian dengan baik, motivasi siswa dalam belajar menulis bahasa Inggris rendah, waktu untuk melihat bagaimana proses menulis siswa oleh guru tidak cukup. Siswa memiliki masalah dalam tata bahasa dan kosa kata. Tujuan penelitian ini untuk mengetahui apa saja tugas penilaian yang diberikan guru dalam mengajar menulis, untuk mengetahui bagaimana guru menilai tugas penilaian menulis siswa dan kemudian untuk mengetahui apa saja masalah guru dalam menilai tugas penilaian menulis di kelas 11 MAS. TI Paninggahan. Dalam penelitian ini menggunakan metode deskriptif kualitatif. Data diperoleh dari wawancara dan analisis dokumen yang dianalisis secara kualitatif. Peneliti menganalisis tugas penilaian menulis siswa yang telah diberi skor dan wawancara dilakukan langsung dengan guru. Temuan dari penelitian ini terdapat beberapa aspek tugas penilaian menulis yang diberikan oleh guru dalam kegiatan kelas selama semester kedua. Terdapat beberapa jenis tugas penilaian yang diberikan guru dalam mengajar menulis. Itu adalah cloze selection task, tugas konstruksi paragraf, dan tanya jawab terbimbing. Selanjutnya peneliti juga menemukan tentang bagaimana guru menilai tugas penilaian menulis yang diberikan. Penilaian dilakukan secara holistik dengan memperhatikan keaslian teks, kesesuaian teks dengan judul, urutan teks, pilihan kosa kata, pilihan tata bahasa, huruf kosa kata dan kerapian teks. Masing-masing poin dirangkai oleh peneliti dari lima poin sampai satu poin berdasarkan aspek sangat sesuai hingga tidak sesuai.